The interwinding nature of protein–protein interfaces and its implication for protein complex formation - Yura, Kei (Oxford University Press, 2009)
Motivation: Structural features at protein–protein interfaces can be studied to understand protein–protein interactions. It was noticed that in a dataset of 45 multimeric proteins the interface could either be described as flat against flat or protruding/interwound. In the latter, residues within one chain were surrounded by those in other chains, whereas in the former they were not. Results: A simple method was developed that could distinguish between these two types with results that matched those made by a human annotator. Applying this automatic method to a large dataset of 888 structures, chains at interfaces were categorized as non-surrounded or surrounded. It was found that the surrounded set had a significantly lower folding tendency using a sequence based measure, than the non-surrounded set. This suggests that before complexation, surrounded chains are relatively unstable and may be involved in ‘fly-casting’. This is supported by the finding that terminal regions are overrepresented in the surrounded set. Availability: http://cib.cf.ocha.ac.jp/DACSIS/ Contact: yura.kei@ocha.ac.jp; sjh@cmp.uea.ac.uk Supplementary information: Supplementary data are available at Bioinformatics online.